The role of fillers in the management of acne scars. (1st June 2017) - Forbat, E.; Ali, F. R.; Al‐Niaimi, F.
Summary: Acne scars are present in 95% of patients with acne, and can cause profound psychosocial morbidity. Fillers are commonly used for facial soft tissue augmentation, and there is increasing interest in their use for the treatment of acne scars, particularly for the atrophic subtype. We review the evidence for the use of temporary, semi‐permanent and permanent fillers for acne scars. The use of permanent methylmethacrylate fillers for acne scarring is supported by a randomized controlled trial, and is approved by the United States Food and Drug Administration. There is initial evidence supporting the use of poly‐L‐lactic acid and hyaluronic acid fillers, but evidence is still lacking about the use of polyacrylamide and polyalkylimide fillers. Abstract : Click here for the corresponding questions to this CME article.